Application of sewage sludge containing environmentally-relevant silver sulfide nanoparticles increases emissions of nitrous oxide in saline soils. (October 2020) - Wu, Jingtao; Bai, Yunfei; Lu, Bingkun; Li, Cui; Menzies, Neal W.; Bertsch, Paul M.; Wang, Zhanke; Wang, Peng; Kopittke, Peter M.
Abstract: Silver (Ag) is released from a range of products and accumulates in agricultural soils as silver sulfide (Ag2 S) through the application of Ag-containing biosolids as a soil amendment. Although Ag2 S is comparatively stable, its solubility increases with salinity, potentially altering its impacts on microbial communities due to the anti-microbial properties of Ag. In this study, we investigated the impacts of Ag on the microbially mediated N cycle in saline soils by examining the relationship between the (bio)availability of Ag2 S and microbial functioning following the application of Ag2 S-containing sludge. Synchrotron-based X-ray absorption spectroscopy (XAS) revealed that the Ag2 S was stable within the soil, although extractable Ag concentrations increased up to 18-fold in soils with higher salinity. However, the extractable Ag accounted for <0.05% of the total Ag in all soils and had no impact on plant biomass or soil bacterial biomass. Interestingly, at high soil salinity, Ag2 S significantly increased cumulative N2 O emissions from 80.9 to 229.2 mg kg −1 dry soil (by 180%) compared to the corresponding control sludge treatment, which was ascribed to the increased abundance of nitrification and denitrification-related genes ( amoA, nxrB, narG, napA, nirS, and nosZ ) and increased relative abundance of denitrifiers ( Rhodanobacter, Salinimicrobium, and Zunongwangia ). Together, our findings show that the application of Ag2 S-containing sludge to a saline soil can disrupt the N cycle and increase N2 O emissions from agroecosystems. Graphical abstract: Image 1 Highlights: The effects of salinity on Ag availability and the soil nitrogen cycle were studied. The availability of Ag2 S increased with salinity. The effects of Ag2 S on the bacterial community composition depended upon salinity. The rate of N2 O emission was linked to Ag availability and N functional genes. Overall, the Ag2 S posed a low risk for plants and soil microbes.